Ekonomi Digital dan Hukum Ekonomi Syariah: E-Commerce, Aset Digital, dan Implikasi Hukumnya Menurut Islam - Nurfakhruddin Al Mubarak; Anugrah Anugrah; Mukhtar lutfi; Darmawati Darmawati (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study aims to analyze the concept of the digital economy, examine the Islamic economic law perspective on e-commerce practices and digital assets, and explain their legal implications from an Islamic perspective. The findings indicate that e-commerce is fundamentally a form of muamalah that is permissible based on the principle of al-ibāḥah al-aṣliyyah, provided that it fulfills the essential elements and conditions of a valid contract and is free from the elements of riba (usury), gharar (excessive uncertainty), maysir (gambling), and tadlis (fraud). Meanwhile, the legal status of digital assets depends on their characteristics, functions, and transaction mechanisms. Cryptocurrencies that qualify as commodities (sil'ah) and are traded in accordance with Sharia principles may be considered permissible, whereas their use as currency or purely speculative instruments involving gharar and maysir is prohibited. The study also reveals that the development of the digital economy offers significant opportunities to strengthen the Islamic economic ecosystem through Sharia-compliant fintech, halal marketplaces, and digital financial innovations. However, it also presents challenges, including the need for stronger regulatory frameworks, improved Islamic financial literacy, and the development of effective Sharia compliance mechanisms within the digital ecosystem. Therefore, the implementation of Islamic economic law principles serves as an essential foundation for ensuring that digital economic activities are conducted fairly, transparently, securely, and in accordance with the objectives of maqāṣid al-sharī'ah.